Kualitas Informasi & Kepercayaan dalam Mendorong Pembelian di Marketplace Facebook - Sarini, Sarini; Sunandar, Suwarto; Kurniadi, Hanif (Universitas Pahlawan Tuanku Tambusai, 2025)
This research explores the effect of information quality and trust on online purchasing decisions in Facebook Marketplace. Employing a quantitative approach, data were gathered through observations, literature reviews, and surveys. The study involved 110 respondents from Kolaka Regency, selected using purposive sampling. Data analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS) via SmartPLS, while validity and reliability tests were performed using SPSS 25. The results indicate that both information quality and trust significantly influence online purchasing decisions. Facebook Marketplace sellers are encouraged to prioritize providing high-quality information and fostering trust with potential buyers. By ensuring transparency, accuracy, and credibility in their listings, along with strategies to strengthen consumer confidence, sellers can attract more customers and boost their online sales effectively.